Object Detection of Ground-Penetrating Radar in the Frequency Domain Using Three-Antenna System - Kittiyanpunya, Chainarong; Krairiksh, Monai (My University, 2022)
An object detection method of ground-penetrating radar (GPR) in the frequency domain using three-antenna system is proposed in this study. The presented methodology utilizes the electromagnetic (EM) scattering from the object for identification using its natural poles. Two schemes of GPR system were examined. The first scheme was the conventional GPR comprising one transmitter and one receiver. The second scheme comprises two transmitters and one receiver, which the transmitters were excited by out-of-phase generators with each other. The simulations were initially performed using the three-antenna system for GPR. The results indicated that the natural poles in the scattering responses changed according to the characteristics of the object. For comparison, the three-antenna system for GPR was fabricated and experimented in comparison with the conventional GPR configuration. The experimental results revealed that the three-antenna configuration was able to mitigate the ground bounce and antenna coupling effects, while the conventional GPR was interfered by the effect of ground reflection and mutual coupling of the antennas. The three-antenna configuration is thus suitable to be the front-end before extracting the natural poles. In addition, the frequency domain method is compatible with the three-antenna system in the determination of the natural poles for identification. As such, the proposed system for investigating the response in the frequency domain is operationally appropriate in GPR system.
Keywords: Cauchy method; ground penetrating radar (GPR); identification of object; radar remote sensing; singularity expansion method (SEM)